Energy Use and Economic Growth in Africa: A Panel Granger-Causality Investigation - Mohamed El Hedi Arouri; Adel Ben Youssef; Hatem M'Henni; Christophe Rault (Center for Economic Studies and ifo Institute (CESifo), 2014)
We make use of a bootstrap panel analysis of causality between energy use and economic growth for a sample of sixteen African countries over the period 1988-2010. Our results show that growth and energy use are strongly linked in Africa. However, African countries are heterogeneous and there is no one way recommendation about energy-growth relationship that may work for all countries in Africa.
Keywords: Q43; Q53; Q56; 330; energy use; growth; VAR